Novel metaphors for a novel school: Narratives, voices and experiences from pre-service teachers engaged in service-learning in Spain - Márquez-García, María Jesús; Leite-Méndez, Analía Elizabeth; Kirsch, William (Elsevier, 2022)
In this article, we analyze a service-learning experience developed in a class of the major in Primary Education Teaching at the University of Malaga, in Andalusia, Spain, by resorting to the metaphors produced by pre-service teachers in the narrative and reflective pieces written for classwork. As a result, we unearthed a constellation of metaphors organized into two main axes: (1) metaphors for school success; (2) metaphors for learning and teaching. In our interpretation, the experience makes it possible for the emergence of novel metaphors which resonate with a more dialogical and solidary educational praxis compared to participants’ own schooling experiences.
https://openpolicyfinder.jisc.ac.uk/id/publication/16763
Keywords: Investigación activa en educación; Profesores - Formación profesional; Teacher education; Service-learning; Metaphors